Analysis of Employee Performance in Periodic Salary Increase Administration Services at the Langkat Regency Regional Civil Service Agency - Nasution, Syafriansyah; Adam, Adam; Warjio, Warjio (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the performance of employees in administrative services for periodic salary increases at the Regional Civil Service Agency (BKD) of Langkat Regency. The research focuses on five main aspects: work quality, quantity of work, responsibility, cooperation, and employee initiative. The research method used is a qualitative descriptive approach, with data collection techniques through in-depth interviews, observations, and documentation. The research informants include BKD employees, periodic salary increases, and administrative services. The study results show that the quality of employees' work is quite good, although speed and transparency need to be improved. The quantity of work is adequate, but high workloads and limitations of administrative systems often hinder services. Employee responsibility and cooperation are high, but further monitoring and coordination are needed. Employee initiatives are positive, but technology optimization is required to support efficiency. By overcoming existing obstacles, administrative services for periodic salary increases at BKD Langkat Regency can be more effective and responsive.